2021
DOI: 10.3389/fpsyg.2021.683684
|View full text |Cite
|
Sign up to set email alerts
|

Mistrust and Beliefs in Conspiracy Theories Differently Mediate the Effects of Psychological Factors on Propensity for COVID-19 Vaccine

Abstract: Vaccination is considered a key factor in the sanitary resolution of the COVID-19 pandemic. However, vaccine hesitancy can undermine its diffusion with severe consequences on global health. While beliefs in conspiracy theories, mistrust in science and in policymakers, and mistrust in official information channels may also increment vaccine hesitancy, understanding their psychological causes could improve our capacity to respond to the pandemic. Thus, we designed a cross-sectional study with the aim of probing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 95 publications
7
106
0
2
Order By: Relevance
“…The size of this zero-order correlation was similar to that of the partial correlation reported by Swami et al (2016) for US participants (.20 versus .15). It is likewise very similar to the correlation of .20 found in Simione et al (2021). Considering our findings along with the existing literature it seems reasonable to infer that there is now robust evidence of a positive relationship between perceived stress and beliefs in conspiracies -but that this correlation is relatively small.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The size of this zero-order correlation was similar to that of the partial correlation reported by Swami et al (2016) for US participants (.20 versus .15). It is likewise very similar to the correlation of .20 found in Simione et al (2021). Considering our findings along with the existing literature it seems reasonable to infer that there is now robust evidence of a positive relationship between perceived stress and beliefs in conspiracies -but that this correlation is relatively small.…”
Section: Discussionsupporting
confidence: 87%
“…An Italian study (Simione et al, 2021) likewise reported a significant correlation (r = .20, p < .01) between perceived stress and belief in conspiracy theories.…”
Section: Introductionmentioning
confidence: 86%
“…The well-being worsening across the two waves in Italy may allow us also to better contextualize other Covid-19 related outcomes and phenomena, like vaccination hesitancy. Indeed, lower well-being appeared connected to belief in conspiracy theories and mistrust in medicine and science, which ultimately may lead to avoiding vaccination [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of respondents (80.2%) reported feeling that social aversion and mistrust towards doctors increased during the pandemic, and many of them (43.3%) claimed that it may affect their enthusiasm about their future job. Although there is very little research about mistrust among patients in Poland fueled by the COVID-19 pandemic, scientists from other countries reported that many people endorse conspiracy theories about the origins of the pandemic [39], and some are hesitant to be vaccinated because of their distrust of political and medical institutions, "anti-establishment" sentiments, and conspiratorial and paranoid beliefs [40,41] and, because of the shortage of healthcare professionals [42][43][44], the need to care for COVID-19 patients and prevent further spread of the virus, the "non-COVID" patients are often left waiting in long queues for telehealth that may not be enough, especially for those with lower socioeconomic backgrounds, who can't afford easy access to the devices needed for telemedicine [45]. All these problems have also been present in Poland and may have contributed to the growth of medical mistrust among polish patients.…”
Section: Plos Onementioning
confidence: 99%